UKURAN PERUSAHAAN SEBAGAI PEMODERASI FINANCIAL PERSPECTIVE DAN TAX AVOIDANCE DI INDUSTRI REKREASI DAN PARIWISATA - Nurul Hasanah Uswati Dewi; Athala Asyifanaya (Jurnal Bisnis dan Akuntansi, 2023)
The research aims to determine the influence of capital intensity, profitability, thin capitalization, and sales growth on tax avoidance using the company size as moderation variables. The research object is a recreation and tourism company listed on the Indonesia Stock Exchange (IDX) from 2017 to 2020. The number of sampled in this research was 68 samples selected with purposive sampling techniques. The data analysis used descriptive statistical analysis and multiple linear regression test with SPSS version 26 application. This study showed that the variable thin capitalization have positive effect on tax avoidance, while capital intensity, profitability, and sales growth variable have no effect on ta x avoidance. In addition, the result of this study based on the moderated regression analysis (MRA) test, the company size variable cannot moderate the influence of capital intensity, profitability, thin capitalization, and sales growth on the tax avoidance.